Analisis Proyeksi Normalisasi Hubungan Arab Saudi-Israel dan Dampaknya bagi Palestina dalam Perspektif Soft Constructivism - Fitriani, Andine; Aqilah, Harwinda Niken Aqilah; Wardani, Rahmalia Ekrinda Ayu; Ismail, Zaky Ismail (Global Political Studies Journal, 2025)
This research aims to analyze the projection of normalization between Saudi Arabia and Israel and its implications for the Palestinian struggle. The tendency toward normalization between the two states has gradually developed since the late 1960s, illustrating how domestic political and security dynamics can reshape Saudi Arabia’s policies, norms, and national identity. The study employs a qualitative research method with a case study approach. Data collection is conducted through library research, drawing from books, e-books, journal articles, and relevant news sources. The findings suggest a significant potential for the establishment of normalized relations between Saudi Arabia and Israel, driven primarily by shared national interests. Furthermore, such normalization is likely to have a profound impact on Palestine, particularly on the ongoing struggle for independence. This research contributes to enriching the discourse on soft constructivism theory in the analysis of foreign policy within the Middle East region Keywords— Israel, Normalization, Palestine, Saudi Arabia, Soft Constructivism.